PENAL MEDIATION IN SOLVING MEDICAL MALPRACTICE CASES AS AN ALTERNATIVE OF PENAL SANCTIONS BASED ON LOCAL WISDOM - Sri Setiawati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In the 1945 Constitution of Indonesia’s preamble, it is stated that in order to form a government of Indonesia, a legal system based on the values of Pancasila is formulated. 1945 Constitution of Indonesia itself becomes the basic law in formulating a rational effort in solving crimes. In other words, the penal policies in Indonesia must also be based on the values of Pancasila in social policies contained in the 1945 Constitution of Indonesia. The formulation of the Bill of Penal Code begins with "the idea of a balance" between the interests of society and individual interests; recognition of the law which serves as a source of law in addition to Act, even justice is served not only by law, but also based on the guidance of the Almighty. Why is Penal Mediation able to be selected to complete the culpa offense case, especially medical malpractice? Mediation is a way of settling penal disputes outside of law in accordance with the desired way the community in resolving the case, namely the peaceful deliberations. Penal mediation gives space to bring the victim and the perpetrators of penal acts together, so that the interests of both parties can be accommodated. Long before the developed countries thought of ADR and policies in a limited and selective use of penal sanctions, the Indonesian people are already familiar with their local wisdom resolve any conflict with deliberations. Keywords: penal-mediation, medical malpractice, local-wisdom